Penerapan Media Gambar Komik dalam Meningkatkan Keterampilan Menulis Teks Cerita Rakyat Pada Siswa Kelas VII SMP Negeri 1 Parung Kabupaten Bogor - Stella Talitha; Dinda Dania Herdiani (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, UNPAK, 2021)
This study aims to determine the application of comic drawing media in improving the skills of writing folklore texts in VII grade students of SMP Negeri 1 Parung Kabupaten Bogor, and to find out the obstacles experienced by students in writing folklore texts. The method used in this research is experiment. Data collection techniques used were tests, non-tests in the form of observation, and questionnaires. The sampling technique is done by way of cluster ramdom sampling. The first hypothesis is the application of comic drawing media can improve the ability to write folklore texts can be tested for truth. This is evidenced by obtaining experimental class pretest data with an average 39,5. From these data it can be seen that the ability of students is in the level of being unable to write folklore texts. Meanwhile, the posttest results increased, The average value of the experimental class in writing folklore texts became 89.9 with a very capable level. This shows a very significant increase in the experimental class that is equal to 50.4. Therefore t0 is Bigger than tt 1,67 more than 2,78 more than 2,38. The second hypothesis is that the obstacles experienced by each student in writing folklore texts are proven true. Based on the results of the questionnaire, which states as much as 38% were experiencing obstacles when writing folklore texts. Then 44% were still experiencing obstacles in compiling the framework of folklore, in developing as a 47% folklore framework, then the obstacles in writing folklore texts through comic drawing media 38%, and the overall obstacle of teaching and learning activities 38%. Thus, the application of comic drawing media can improve writing skills of folklore texts in class VII students of SMP Negeri 1 Parung Kabupaten Bogor. Although there are some obstacles in the process, in the end students are able to write folklore texts through the media of comic drawings.